Produção e processo de Downstream de lipopeptídeos fungicidas produzidos pelo Bacillus subtilis CNPMS 22 - Souza, Caroline Gondim de (2019)
The search for natural products capable of controlling phytopathogens is a growing need because of concern for both food safety and the environment. In this context, Bacillus subtilis stands out due to its potential in producing a large variety of lipopeptides with antifungal activity. Therefore, the general objective of the present work was to quantify, purify and verify the fungicidal action of the lipopeptides produced by the B. subtilis CNPMS 22. A lipopeptide quantification method was initially developed and validated in ultra-performance chromatography with a quadrupole detector ( UPLC-QDA) with the ion monitoring mode (SIM). SIM mode was used to detect and quantify lipopeptides exhibiting [M + H] + ions for iturins and surfacins and [M + 2H] 2+ for fengicins. The monitored ions were: m / z 1043.5; 1057.5; 1071.5; 718.3; 725.4; 739.4; 732.4; 746.4; 753.4; 1008.6; 1022.6 and 1036.6. The compounds were separated by reverse phase liquid chromatography using a C18 analytical column in a total time of 19 min. Later, a scale-up study of the fractionation of lipopeptide families using high-performance liquid chromatography (HPLC) was performed, both on the semi-preparative scale and the preparative scale. The use of the liquid-liquid partition in the separation of the compounds was also evaluated and the feasibility of partitioning with the HPLC was verified, both on a semi-preparative scale and on a preparative scale. For scaling tests with HPLC different loads were used (20, 40, 60 and 80 mg). In this stage the solvent consumption, productivity and yield were evaluated. In the partition was carried out tests of proportions of solvent aiming to determine the ideal condition for the separation of lipopeptides. Then, a study was carried out to evaluate the fungicidal activity of lipopeptide families and crude extract against Colletotrichum musae (anthracnose agent), Fusarium pallidoroseum (fusariosis agent) and Lasiodiplodia caatigensis (resting agent agent). minimum inhibitory concentration (MIC) and cytotoxicity were verified. The results showed that the proposed analytical method of quantification was able to simultaneously quantify 12 isoforms and homologous series of lipopeptide families in biological samples. Regarding the scaling-up study, the results indicated that the magnification of the injection load can be performed up to 60 mg, in both scales. Comparing the results obtained between the scales, it was observed that in the preparative scale the solvent consumption was 4 times higher (4.35 mL mg-1) when compared to the semi-preparative scale (1 mL mg-1). productivity was 2 times higher (0.0084 kg day-1 kg-1), this for the 60 mg load. Satisfactory results were presented by the liquid-liquid partition in the individual surfactin family. The study of the association of HPLC with the liquid-liquid partition revealed that the association is advantageous when working on a preparative scale and initially partitioning 20 mg of the crude extract. The results of the evaluation of the fungicidal activity showed that the fengicin family is ideal for combating the fusariosis agent, since it presented the lowest MIC with 0.0002 mg mL-1 and the surfactin family to combat the anthracnose agent , because it presented the lowest MIC, with 0.0003 mg mL-1. The low cytotoxicity of the fractions reveals a positive result for the applicability of the lipopeptides in the control of phytopathogens, since they did not affect the human cells. In view of the above, it can be concluded that B. subtilis CNPMS 22 provides an alternative bio-resource for the control of phytopathogens, since the lipopeptides produced have antifungal activity and can be used with a natural defensive agent.